SAT0472 Role of MRI in the Follow-up of Patients with Myositis. (9th June 2015) - Pipitone, N.; Notarnicola, A.; Spaggiari, L.; Scardapane, A.; Levrini, G.; Iannone, F.; Lapadula, G.; Zuccoli, G.; Salvarani, C.
Abstract : Background: MRI is widely used to evaluate muscle inflammation in myositis. Muscle edema on STIR sequences is thought to reflect active inflammation. However, it is unclear how useful MRI is in following up patients with myositis, in particular which is its sensitivity to change after treatment onset or intensification. Objectives: To assess changes in MRI muscle edema and to correlate MRI edema score with serum creakine kinase (CK) and muscle strength in a cohort of patients with myositis at their first presentation to our centers (T0) and at follow-up after onset/intensification of immunosuppressive therapy (T1). Methods: We enrolled in 2 Rheumatology centers 36 patients, 17 with dermatomyositis (DM) and 19 with polymyositis (PM) diagnosed according to Bohan and Peter criteria. In all patients, CK was measured, manual muscle test (MMT) was performed and MRI sequences were acquired within a week. MRI edema (1= present, 0= absent) was assessed bilaterally in 17 thigh and pelvic floor muscles. An MRI composite edema score (0-17) was calculated by adding the separate scores bilaterally and dividing them by two as described elsewhere (1). The CK upper limit of normal was 190 U/l. The (single measures) intraclass correlation coefficient (ICC) between the Radiologists involved was 0.78. Muscle strength was measured by MMT and graded according to the Medical Research Council extended scale (0-5). The ICC between the 2 physicians performing the MMT was 0.8. Analysis was performed by Wilcoxon sum rank and Spearman's tests, as appropriate. Results: Mean age (years ± SD) was 54±15. The ratio F:M was 31:5. MRI was positive (edema score ≥1) in 26 (72%) patients at T0 and in 18 (50%) at T1. Mean MRI edema score was 5±5.2 (mean ± SD) at T0 and 2.4±4.5 at T1 (p=0.002). Median and interquartile range (IQR) of MRI edema score were 3.5 (8) at T0 and 0.5 (4.5) at T1. CK was elevated in 22 (61%) patients at T0 and 10 (28%) at T1. CK was 1, 816±3, 560 at T0 and 531±1, 536 at T1 (p=0.002). MMT score was 4.4±0.44 at T0 and 4.6±0.40 at T1 (p=0.02). MRI edema score did not correlate with CK or MMT scores neither at T0 nor T1. Eleven patients had a normal CK but a positive MRI at T0. In 5 of these patients, MRI became negative at T1. In the 11 patients with a normal CK but positive MRI at baseline, MRI edema score decreased from 6.7±5.3 at T0 to 2.4±2.7 at T1 (significance not calculated because of the small sample size). Conclusions: MRI is a useful tool to monitor patients with myositis, and might particularly have a role in monitoring disease activity in patients with a normal serum CK at baseline. Larger studies are required to confirm our findings. The last 2 authors share senior authorship References: Clin Exp Rheumatol 2012; 30:570-3 Disclosure of Interest: None declared